Hubungan Gagal Ginjal Kronik dengan Diabetes Mellitus Tipe 2 - Tarigan, Gracecilia; Tarigan, Pengarapen; Siahaan, Jekson Martiar (Jurnal Kedokteran Methodist, 2020)
Background : Many factors can cause chronic kidney disease, namely DM, Hypertension, Polycystic Kidney Disease, Chronic Interticial Nephritis. The results of the 2018 Riskesdas the prevalence value of chronic kidney disease in Indonesia was 3.8% and increased by 1.8% from 2013 data. In DM patients, kidney disorders can be found, kidney disorders can be a complication that causes a decrease in the patient's quality of life. Disorders that occur in the kidneys due to diabetes are characterized by the appearance of microalbuminuria, which means that the amount of albumin excretion in the urine between 20 and 199 ug / minute. The aim of this study was to determine the relationship between type 2 diabetes mellitus and chronic kidney disease. Methods : The research method used was a Literature Review, using secondary data. The data were collected using a documentation techniques. The research journals used were 6 journals with inclusion criteria for the publication date of the last 5 years, the language used was Indonesian or English, with the research subjects of patients with a diagnosis of chronic kidney disease with type 2 diabetes mellitus and a full text publication. Conclusion : There is an association between diabetes mellitus type 2 with chronic kidney disease which can be seen in (microalbuminuria, Blood sugar rate, Hypertension and HbA1C)